LIMITATIONS OF MUSLIM WOMEN'S VOICES IN ISLAMIC VIEWS : (Study of Tafsir Surah Al-Ahzab Verse 32) - Herman, Herman; Sarifuddin, Agus; Yasyakur, Muhammad (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Women or women created by Allah are weak creatures in terms of nature and creatures that Allah SWT and His Messenger mention is a slander for their hearts to be damaged and prone to follow lust, so that it is easy and easy to be deceived by women, especially the voices caused by women. This study aims to examine how the views of interpretation scholars are related to voice and voice limitations for women. The method used in this study is a qualitative method, with a literature study. The result of this study is that the scholars have various opinions with various levels and times as well as to whom and when a woman speaks softly, politely, and firmly, but it is forbidden to speak in a rowful or weak manner so as to cause desire in those who hear it, especially those who are adams, and it is better to speak firmly to the adams. But the intonation of speaking was firm.